Accessory gallbladder in an intrahepatic location mimicking a cystic tumor of the liver: A case report. Issue 44 (November 2016) - Won, Ji-Hye; Choi, Seo-Youn; Lee, Hae Kyung; Yi, Boem Ha; Lee, Min Hee; Jung, Min Jung
Abstract: Background: Double gallbladder (GB) is a rare congenital anomaly of the biliary system characterized by the presence of an accessory GB. Clinical Findings: A 38-year-old female presented with a history of right upper quadrant (RUQ) pain. Computed tomography (CT) showed a lobulated cystic mass involving the center portion of liver. Magnetic resonance imaging (MRI) additionally revealed a tubular structure of T2 bright signal intensity (SI), which connected the cystic lesion of the liver to the bile duct. Preoperative endoscopic retrograde cholangiopancreatography (ERCP) confirmed the connection between the intrahepatic cystic lesion and the left main hepatic duct. We regarded as a cystic mass with biliary communication, such as a cystic intraductal papillary neoplasm of the bile duct (IPNB) or localized Caroli disease. The patient underwent partial hepatectomy for the cystic mass of the liver and a final diagnosis of chronic inflammation of an intrahepatically located accessory GB was made. Conclusion: We report a case of an accessory GB in an intrahepatic location mimicking a cystic mass such as cystic IPNB or localized Caroli disease of the liver showing a cystic mass with biliary communication.